Sorprendente Perú : colección fotográfica de un país extraordinario - Macchione, Ezio; Universidad Peruana de Ciencias Aplicadas (Lima : Editorial UPC, 2019)
The book comprises the photographic collection of Ezio Macchione (b. Italy, lives and works in Peru) that brings together 72 amazing images -most of them of vertical forma- about landscapes and unexplored nature in the jungle, mountains and coast of Peru, where the focus, interpretation and selection of photographs differ from the traditional iconography with which it is represented Peru.
Prólogo -- Presentación -- Sierra -- Selva -- Desierto -- Costa.
In Spanish.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Fotografía de paisajes -- Perú.; Landscape photography -- Peru; Peru -- Description and travel; Peru -- Pictorial works; Perú -- Descripción y viajes; Perú -- Obras pictóricas.; Libros electrónicos.